Computer Tools for Diagnosing Citrus Leaf Symptoms (Part 2): Smartphone Apps for Expert Diagnosis of Citrus Leaf Symptoms - Arnold Schumann; Laura Waldo; Perseveranca Mungofa; Chris Oswalt (EDIS, 2020)
Visual identification of nutrient deficiencies in foliage is an important diagnostic tool for fine-tuning nutrient management of citrus. This new 2-page article describes a new smartphone app that uses a trained neural network to identify disease and pest symptoms on citrus leaves through your phone's camera. Written by Arnold Schumann, Laura Waldo, Perseveranca Mungofa, and Chris Oswalt, and published by the UF/IFAS Department of Soil and Water Sciences. https://edis.ifas.ufl.edu/ss691